Formation of tetrahydro-ß-carbolines and ß-carbolines during the reaction of L-tryptophan with D-glucose - Rönner, Birgit; Lerche, Holger; Freilinger, Christine; Bergmüller, Wolfgang; Severin, Theodor; Pischetsrieder, Monika (Journal of Agricultural and Food Chemistry, 2000)
The reaction of L-tryptophan (Trp) with D-glucose under conditions that can occur during food processing and preparation was studied by high-performance liquid chromatography with diode array detection (HPLC/DAD). Besides the well-established glucose-tryptophan Amadori product (AP), (1R,3S)-1-(D-gluco-1,2,3,4,5-pentahydroxypentyl)-1,2,3,4-tetrahydro-beta-carboline-3-carboxylic acid (PHP-THbetaC) was identified as an important product of this reaction. For preparation, PHPTH betaC was obtained in high yields when Trp and D-glucose were reacted under strongly acidic conditions after heating in methanol. At elevated reaction temperatures (150 °C) 1-acetyl-beta-carboline (acetyl-betaC), was detected in significant concentrations. The mixtures were heated under variations of reaction time and temperature, and AP, PHP-THbetaC, and acetyl-betaC were quantified. In the presence of air oxygen or mild, food relevant oxidants, such as L-dehydroascorbic acid, PHP-THbetaC was readily oxidized to a product that was identified as the previously unknown 1-(D-gluco-1,2,3,4,5-pentahydroxypentyl)- beta-carboline (PHP-betaC). Formation of PHP-THbetaC and PHP-betaC in foodstuffs would deserve particular interest because multiple physiological activity of THbetaC and betaC derivatives has been shown previously.
UnivIS-Import:2015-03-06:Pub.2000.nat.dchph.llmch.format
Keywords: Maillard reaction; tryptophan; tetrahydro-beta-carboline; beta-carboline